The Practicality of Embedding Digital Technology In Pre-Service EFL Teacher - Rahman, Muthia; Sandra, Haris (Modality Journal: International Journal of Linguistics and Literature, 2024)
This research examines how pre-service teachers in Bukittinggi are taught and learn in their teaching practicum by using digital technology in the classroom. The focus of the study is on the obstacles they face due to the lack of teaching resources and the importance of using technology comprehensively, where teaching methodology and subject matter work together. Six pre-service teachers in Bukittinggi were invited to participate in the case study approach used in this research, which aims to gain an in-depth understanding of their experiences. Data was collected through video recordings of their teaching and learning process, in-person observations, interviews, and analysis of their lesson plans and teaching materials. Despite the pre-service teachers having strong knowledge and experience in using technology for classroom teaching, they often encounter difficulties when trying to implement it. This is primarily due to problems with the school's technology, poor internet connection, and limited support from their advisors. As a result, the pre-service teachers still prefer to use advanced technology devices and conventional teaching methods. The research highlights a significant difference between what the pre-service teachers have learned and how they apply it in their teaching practices. To help teachers use technology more efficiently, schools need to enhance their technology infrastructure and support. Penelitian ini mengkaji mengenai bagaimana para calon guru di Bukittinggi menerapkan proses pengajaran dan pembelajaran dalam praktik belajar mengajar mereka menerapkan teknologi digital di kelas. Penelitian ini berfokus pada tantangan yang dihadapi terhadap keterbatasan sumber daya pengajaran dan integrase penggunaan teknologi yang penting dilakukan secara komprehensif terhadap metode pengajaran, dan materi pelajaran. Terdapat enam mahasiswa yang merupakana calon guru di Bukittinggi yang dipilih sebagai responden dari penelitian ini. Penelitian ini merupakan penelitian studi kasus untuk mengkaji secara mendalam mengenai pengalaman mereka dalam mengintegrasikan teknologi digital dalam proses belajar mengajar. Pengumpulan data dilalukan melalui perekaman video terhadap proses pengajaran dan pembelajaran dan obeservasi langsung, interview, serta analisis rencana pelajaran dan bahan pengajaran mereka. Meskipun mereka  memiliki pengalaman dan pengetahuan yang kuat tentang penggunaan teknologi untuk pengajaran kelas, mereka sering menghadapi kesulitan dalam menerapkannya ke dalam praktik kelas. Hal ini disebabkan oleh beberapa masalah tentang teknologi sekolah, koneksi internet yang buruk, dan keterbatasan dukungan dari guru pamong mereka. Hal itu menyebabkan penggunaan perangkat teknologi dan cara pengajaran konvensional masih lebih disukai untuk diterapkan oleh mereka. Penelitian menunjukkan bahwa terdapat perbedaan yang signifikan antara apa yang telah dipelajari oleh calon guru dengan penerapannya dalam praktik pengajaran mereka. Untuk membantu guru menggunakan teknologi secara lebih efisien, sekolah harus meningkatkan teknologi dan dukungan mereka. Kata Kunci:  mahasiswa calon guru, teknologi, praktek mengajar